Pengaruh Pemeliharaan Mesin Terhadap Kualitas Sepatu Pada Pt. Nikomas Gemilang - Maria Anggraini; Rahmat Maulana (FEB Universitas Sultan Ageng Tirtayasa, 2016)
The purpose of this research is to find out and analyze the effect of engine maintenance to quality shoes PT. Nikomas Gemilang. The population in this study are all employees of PT Gemilang Nikomas building 11 part Assembling. The number of as many as 150 employees and population samples taken as many as 109 employees of PT. Nikomas building 11 Scintillating Part Assembling. Methods of analysis used in this research is descriptive and analysis method of quantitative analysis by a simple linear regression analysis. The data processing is done using the application program SPSS version 15.00 for windows. Based on the results of the analysis by using the IBM SPSS software version 15.00 for windows test results of t, where t is a value count 2.543 > t table significance of 1.98 and tables are of significance (0.00) under the (smaller) than 0.05. On testing the determination of the koefesien R = 0,436 showed the influence of strong enough. The relationship between maintenance (X) against the variable quality of shoes (Y) on the employees of PT. Nikomas Gemilang amounting to 94% meaning that showed a very strong relationship and the rest 6% is explained by other variables not examined as factors ability, work discipline, attitude, work ethic, technology earnings. Etc.